ANALYSIS OF HYGIENE AND SANITATION IN CHICKEN SLAUGHTERHOUSES IN JAMPANG VILLAGE, BOGOR REGENCY, WEST JAVA PROVINCE, INDONESIA - Haq, Ainul; Ayunda, Ratry; Puspitasari, Riris Lindiawati (International Journal of Biosciences and Biotechnology, 2021)
This chicken slaughterhouse in Jampang Village is a home industry that is engaged in chicken slaughter. The problem in this research is the process of slaughtering chickens that do not meet the standards. The purpose of this study was to identify the hygiene and sanitation of chicken slaughterhouses. Data collection was done by filling out questionnaires and observations. The observation sheet is made based on SNI-01-6160-1999 concerning Poultry Slaughterhouses (Badan Standarisasi Nasional, 1999). The observation sheet was used to assess the hygiene and sanitation conditions using the scoring method. This study used  descriptive statistics to analyze the abserved data. The scoring method is done by determining the weight for each variable and determining the value for each of the assessed aspects. The results showed that the workers were in good health. Not yet using boots, masks, aprons and headgear. The building is still integrated with the residence. The layout is not in line with the flow of the production process. Sewerage drain is readily available. The cage has never been washed using water and detergent. The conclusion is that the hygiene of the chicken cutters and the sanitation of the buildings still do not meet the requirements. The proposal for improvement is the health of chicken slicers and the use of equipment are things that need to be considered, the building must be separated from the residence, the layout should be improved in the direction of the production process, the building construction is made rodent-free, the chicken coop must be cleaned regularly with water and detergent.